1984
DOI: 10.1002/chin.198408205
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A NEW SYNTHESIS OF SUBSTITUTED 2(1H)‐PYRAZINONES

Abstract: Aminonitrilhydrohalogenide (I) und Oxalylchlorid (II) ergeben über (III) die Pyrazinone (IV), die in einer Tabelle aufgeführt sind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…chloride (14). A mixture of 11 (4.0 g, 30.0 mmol) and 10% Pd/C (3.08 g) in ethanol (80 mL), methanol (30 mL), concentrated HCl (6 mL), and water (10 mL) was shaken on a Parr apparatus at 60 psi for 25 h. The reaction was filtered through Celite, rinsing with 1:1 ethanol/methanol, and was evaporated in vacuo to a solid, which was triturated with 5:1 ethyl acetate/ ethanol to give the title compound (5.95 g, 94%): 1 H NMR (CD3OD) δ 2.58 (s, 3 H), 4.12 (s, 2 H), 6.92 (d, J ) 9.2 Hz, 1 H), 7.93 (d, J ) 9.2 Hz, 1 H).…”
Section: -(2-phenethylamino)-6-methyl-1-(2-amino-46-dimethyl-5-methyl...mentioning
confidence: 99%
See 1 more Smart Citation
“…chloride (14). A mixture of 11 (4.0 g, 30.0 mmol) and 10% Pd/C (3.08 g) in ethanol (80 mL), methanol (30 mL), concentrated HCl (6 mL), and water (10 mL) was shaken on a Parr apparatus at 60 psi for 25 h. The reaction was filtered through Celite, rinsing with 1:1 ethanol/methanol, and was evaporated in vacuo to a solid, which was triturated with 5:1 ethyl acetate/ ethanol to give the title compound (5.95 g, 94%): 1 H NMR (CD3OD) δ 2.58 (s, 3 H), 4.12 (s, 2 H), 6.92 (d, J ) 9.2 Hz, 1 H), 7.93 (d, J ) 9.2 Hz, 1 H).…”
Section: -(2-phenethylamino)-6-methyl-1-(2-amino-46-dimethyl-5-methyl...mentioning
confidence: 99%
“…Compound 2 was found to be air-sensitive, like a previous phenethylamino- pyridinone, 11 and could not be isolated absolutely pure using normal laboratory practices. We are aware of only one published method for the synthesis of 3-aminopyrazinones, that of Hoornaert et al 14 who showed that the HCl salt of an N-alkyl-Raminonitrile reacts with oxalyl chloride in hot o-dichlorobenzene to give an intermediate 1-alkyl-3-hydroxy-5chloropyrazinone. This reacts with a second equivalent of oxalyl chloride to give, in one operation, the 1-alkyl-3,5-dichloropyrazinone.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of alkylamine hydrochlorides 8 with chloroacetonitrile in the presence of potassium iodide and potassium carbonate in acetonitrile afforded cyanomethylamines 9 in high yield. The cyanomethylamine intermediate was then heated in the presence of oxalyl chloride in toluene at 55 °C to form dichloropyrazinone intermediates 10 . For analogues with an ether moiety in the R 1 group, improved yields were obtained by heating the reaction mixture at 55 °C in a mixture of dioxane and dichloromethane.…”
Section: Resultsmentioning
confidence: 99%
“…General Procedure for the Preparation of 3-Phenylaminopyrazin-2(1H)-ones (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). A mixture of 3,5dihalopyrazin-2-one (5 mmol), aniline (7.5 mmol), and 10camphorsulfonic acid (5 mmol) in i-PrOH was refluxed for 48 h. After cooling the reaction mixture the precipitate was collected by filtration and successively washed with i-PrOH, aqueous potassium carbonate, water, and diethyl ether.…”
Section: Methodsmentioning
confidence: 99%
“…The condensation of the hydrochloride salt of 5 with oxalyl chloride to form the corresponding 3,5dichloropyrazinone 9 was effected according to a procedure described previously. 10,11 Substitution of the reactive imidoyl halide moiety in the C3-position of the 2(1H)-pyrazinones 6-9 with 4-aminobenzonitrile in the presence of camphorsulfonic acid as a catalyst gave the key precursors 10-14 (Scheme 1). The 3-anilino analogues 15-20 were obtained by conversion of 6 and 7 with different anilines under the same reaction conditions (Scheme 2).…”
Section: Chemistrymentioning
confidence: 99%